Investigating the product life cycle of Snap and its sports media partnerships - Hambrick, Marion E. (London : SAGE Publications: SAGE Business Cases Originals, 2019)
In 2018, Snap leaders faced challenges such as negative public responses to the redesign of the Snapchat smartphone application, lackluster demand for Spectacles, revenue streams limited primarily to advertising, and no expectation of profits in the immediate future. These issues, associated with a saturated market and slowing growth, were reflected in the company stock price, which fell from a high of USD 29.44 in February 2017 to a record low of USD 10.50 in May 2018. Company leaders needed ways to manage these issues and ultimately generate a profit. Partnerships within the sports industry, including with media providers and sports leagues, represented one potential opportunity. Using the product life cycle framework, students are asked to evaluate the current and future potential of Snap for success with its various product lines, including its foray into sports.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Snap Inc. -- Case studies; Snapchat (Electronic resource) -- Case studies; Internet industry -- United States -- Case studies; Mass media and sports -- United States -- Case studies